RANCANG BANGUN APLIKASI VIRTUAL REALITY (VR) SISTEM TATA SURYA SEBAGAI MEDIA PEMBELAJARAN SAINS - Feri Susilawati; Munzir Umran; Galang Pandu Pratama (Politeknik Aceh, 2021)
Currently, study about solar system a that is reading books. which are considered monotonous and unattractive, thereby reducing students' interest in learning. Virtual Reality (VR) applications are offered to attract students' interest in learning and can facilitate learning by adding visualizations for delivering material related to the solar system. This application was developed by delivering information in the form of text and 3D animation by presenting knowledge to users such as the distance of the planet to the Sun, diameter, layers, and the constituents of the planet. The Solar System VR Application as a Science Learning Media is effective for facilitating learning related to the solar system.